Health service maladministration's in the covid-19 pandemic era - A Basuki Babussalam (Faculty of Law, University of Muhammadiyah Malang, 2020)
This study examines the actions of maladministration frauds in health services particularly in the condition of Covid-19. This study aims to formulate which health services are categorized as maladministration, notably during the Covid-19 pandemic. The method used in this study is a normative research method followed by three approaches. Those approaches are the statutory approach, conceptual approach, and historical approach. The outcomes of this study indicate that the condition of the Covid-19 pandemic has opened some opportunity for maladministration fraud in the field of health services. Given the importance of public health services, notably during the Covid-19 pandemic, it is highly important to anticipate the maladministration frauds to not massively occur. When the acts of maladministration frauds still occur although attempts to prevent it have been carried out, hence the law must be present to provide justice. This paper also elucidates about actions need to be taken so that law enforcement related to maladministration frauds in the field of health services can be solved